Digital Marketing Strategy in Admitting New Students during COVID 19 in Maritime Educational Institutions-An Empirical Study - D. Rajasekar; P. S. Aithal, (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: The goal of this study is to determine how digital marketing affected student enrollment at maritime educational institutions in the year COVID 19. Design/Methodology/approach: Students at Chennai's marine educational institutions made up the target demographic. Data gathered from 96 students using an electronic questionnaire. Findings: Results showed that digital marketing is positively related to students' admission to the business administration degree. Practical Implications: This study has specific implications for colleges that will help them create a digital marketing strategy to help them admit more students to their business administration programmes during COVID 19. In order to make it easier for students to enroll in maritime education, it offers advice for maritime educational institutions on how to execute digital marketing extremely efficiently. Originality/Value: This paper makes a significant literary addition to the field of digital marketing. It is distinctive in that it incorporates the use of various marketing techniques with pupils, strengthening the maritime education in the process. Type of Paper: Case Study & Analysis.